2013
DOI: 10.18052/www.scipress.com/ilcpa.14.146
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents and Insecticidal Activity of <i>Senna italica</i> Mill. from the Sudan

Abstract: The chemical constituents and insecticidal activity of the pods of Senna italica (Caesalpiniaceae, Fabaceae) were investigated. From the chloroform extract of pods, physcion, chrysophanol, chrysophanol-10,10′-bianthrone, chrysophanol-physcion bianthrone and chrysophanolisophyscion bianthrone, were isolated and characterized using different spectral methods. The GC-MS of the n-hexane extract revealed that the major chemical constituents of the oil were 2,6,-di-secbutylphenol (36.69 %), di-n-octylphthalate (12.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The n-hexane extract of the pods of Senna italica Mill. (Fabaceae) caused 100% mortality in adults of Callosbruchus analis F. (Coleoptera: Chrysomelidae) (Yagi et al 2013). The leaf extract from Senna obtusifolia (L.) H.S.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The n-hexane extract of the pods of Senna italica Mill. (Fabaceae) caused 100% mortality in adults of Callosbruchus analis F. (Coleoptera: Chrysomelidae) (Yagi et al 2013). The leaf extract from Senna obtusifolia (L.) H.S.…”
Section: Discussionmentioning
confidence: 99%
“…Previous phytochemical studies have allowed the identification of a variety of compounds found in Senna spp., including alkaloids (Moo-Puc et al 2007), anthraquinones (Branco et al 2011), cardiac glycosides (Essiett & Bassey 2013), glucosides (sennosides) (Monkheang et al 2011), naphthopyrones (Graham et al 2004), phenols (Viegas Junior et al 2013, saponins (Oluwole et al 2016), triterpenes, (Luximon-Ramma et al 2002, among others. The metabolic content of Senna species has been associated with a variety of biological properties, including insecticidal activity (Yagi et al 2013;de Souza Tavares et al 2014;Vasudev et al 2015). Senna crotalarioides (Cassia crotalarioides Kunth [Fabaceae]) is an arborous species distributed in various states of Mexico (Estrada et al 2004).…”
Section: Palabras Clave: Botánico; Gusano Cogollero De Maíz; Insecticmentioning
confidence: 99%
“…Worth mentioning that the plant's root ethyl acetate extract exhibited anti-tick activity against adults of Hyalomma marginatum rufipes [39]. In addition, chloroform extract of pods had insecticidal activity [40]. The antibacterial activity of the leaf and root extracts of Senna italica showed potent activity against several bacterial species [38].…”
Section: B Senna Italicamentioning
confidence: 99%
“…Khalaf et al reported the isolation of tinnevellin; emodin, physcion, 2-methoxy-emodin-6-O-β-D-glucopyranoside, 1,6,8-trihydroxy-3-methoxy-9,10-dioxo-9,10-dihydroanthracene, and rutin from C. italica growing in Egypt ( Khalaf et al, 2019 ). 10,10‘-Chrysophanol bianthrone, chrysophanol, 1,1,8,8‘-tetrahydroxy-6′-methoxy-3,3‘-dimethyl-10,10‘-bianthracen-9,9‘-dione, physcion, and 1,1,8,8‘-tetrahydroxy-7‘-methoxy-3,3‘-dimethyl-10,10‘-bianthracen-9,9‘-dione were separated from C. italica pods growing in Sudan ( Yagi et al, 2013 ). Moreover, (22E)-3-β-hydroxycycloart-22-en-24-one, uvaol, β-sitosterol, daucosterol, emodin, methyl 3,4-dihydroxybenzoate, aloin, 4-hydroxypheny-O-β-D-glucopyranoside, and rutin were repoted from aerial parts of Saudi C .…”
Section: Introductionmentioning
confidence: 99%